Innovations In Strategic Management For Sustainable Business Transformation - Tria Monika Sari (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The dynamics of the global market and increasingly complex environmental pressures make innovation in strategic management a key driver in promoting sustainable business transformation. The role of strategic innovation serves as an adaptive approach capable of integrating economic, social, and environmental aspects into business strategy planning and implementation. By reviewing various literature and recent case studies, this study demonstrates that organizations that adopt innovation in strategic management-such as the use of digital technology, circular business models, and stakeholder-driven approaches-are better able to create long-term value and enhance competitiveness. Furthermore, sustainable transformation requires visionary leadership, an agile organizational culture, and performance measurement systems aligned with sustainability goals. The results of this study are expected to provide both conceptual and practical contributions for companies seeking not only to survive, but also developing in the transition era towards a green and inclusive economy. This study concludes that strategic innovation plays a pivotal role in driving sustainable business transformation within the complex global market.